Fatigue properties of friction stir welded joint of ultrafine-grained 2024 aluminium alloy. (17th February 2017) - Wang, W.; Qiao, K.; Wu, J.L.; Li, T.Q.; Cai, J.; Wang, K.S.
Abstract : Ultrafine-grained (UFG) 2024 aluminium alloy prepared by the equal channel angular pressing was friction stir welded (FSW). The high cycle fatigue and crack growth behaviour of the FSW joint were investigated in air and NaCl solution, respectively. This study demonstrated that FSW was a viable technique for joining UFG materials. The UFG microstructure was retained in the nugget zone (NZ). Compared with the UFG base metal (BM), FSW joint exhibited lower ultimate tensile strength and hardness, and the minimum hardness value was located in the heat affected zone (HAZ). NaCl solution significantly reduced the fatigue strength of FSW joint. Fatigue crack propagation rates in the NZ and HAZ were slower than that in the BM in the whole fatigue life.